2019
DOI: 10.5758/vsi.2019.35.3.137
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Transverse-Incision ‘Mini’ Carotid Endarterectomy and Patch-Plasty

Abstract: PurposeTraditional exposure for carotid endarterectomy (CEA) involves making a longitudinal incision parallel to the anterior border of the sternocleidomastoid. Such incisions can be painful, aesthetically displeasing, and associated with a high incidence of cranial nerve injury (CNI). This study describes the outcomes of CEA performed through small (<5 cm long), transversely oriented incisions located directly over the carotid bifurcation, as identified by color-enhanced Duplex ultrasound.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…To decrease neurologic deficits and improve cosmetic effects, some centers have used minimal longitudinal incisions in a conventional manner, with or without sonographic assistance [2,6]. Furthermore, transverse incisions camouf laged in a skincrease have also been investigated [3,[7][8][9]. Studies of vertical incisions in CEA have shown that a minimal incision causes fewer local neurologic complications than a conventional incision, but no statistical differences have been observed in the incidence of stroke and death [2,6,10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To decrease neurologic deficits and improve cosmetic effects, some centers have used minimal longitudinal incisions in a conventional manner, with or without sonographic assistance [2,6]. Furthermore, transverse incisions camouf laged in a skincrease have also been investigated [3,[7][8][9]. Studies of vertical incisions in CEA have shown that a minimal incision causes fewer local neurologic complications than a conventional incision, but no statistical differences have been observed in the incidence of stroke and death [2,6,10].…”
Section: Discussionmentioning
confidence: 99%
“…To decrease neurologic deficits and improve cosmetic effects, some centers have used minimal longitudinal incisions in a conventional manner, with or without sonographic assistance [ 2 , 6 ]. Furthermore, transverse incisions camouflaged in a skin-crease have also been investigated [ 3 , 7 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the key area for wound breakdown that is why it is important to achieve good hemostasis and carefully suturing the wound. Trifurcations or incisions parallel to carotid artery should be avoided to minimize wound breakdown 18 . Additionally, skin flaps should be elevated in the sub-platysmal plane in order to maximize the blood supply.…”
Section: Discussionmentioning
confidence: 99%